2005
DOI: 10.1109/tnsre.2004.841881
|View full text |Cite
|
Sign up to set email alerts
|

A parametric feature extraction and classification strategy for brain-computer interfacing

Abstract: Parametric modeling strategies are explored in conjunction with linear discriminant analysis for use in an electroencephalogram (EEG)-based brain-computer interface (BCI). A left/right self-paced typing exercise is analyzed by extending the usual autoregressive (AR) model for EEG feature extraction with an AR with exogenous input (ARX) model for combined filtering and feature extraction. The ensemble averaged Bereitschafts potential (an event related potential preceding the onset of movement) forms the exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 17 publications
0
65
0
2
Order By: Relevance
“…For single trial EEG, signals relevant to movement are usually very small compared with ongoing background activity. Studies have attempted to classify whether the subject intended to move the right or left hand during the production of real or imagined movement from single trial EEG (Burke et al 2005;Blankertz et al 2006;Congedo et al 2006;Pfurtscheller et al 2006). They suggested that advanced signal processing and pattern recognition techniques are necessary to extract the relevant signal from single trial EEG.…”
Section: Introductionmentioning
confidence: 99%
“…For single trial EEG, signals relevant to movement are usually very small compared with ongoing background activity. Studies have attempted to classify whether the subject intended to move the right or left hand during the production of real or imagined movement from single trial EEG (Burke et al 2005;Blankertz et al 2006;Congedo et al 2006;Pfurtscheller et al 2006). They suggested that advanced signal processing and pattern recognition techniques are necessary to extract the relevant signal from single trial EEG.…”
Section: Introductionmentioning
confidence: 99%
“…They require an a priori choice of the structure and order of the signal generation mechanism model. (Anderson & Sijercic, 1996;Schlogl et al, 1997;Anderson et al, 1998;Roberts & Penny, 2000;Burke et al, 2005;Vidaurre et al, 2007). AR methods assume that a signal X(t), measured at time t, can be modeled as a weighted sum of the values of this signal at previous time steps, to which we can add a noise term E t (generally a Gaussian white noise):…”
Section: Parametric Modellingmentioning
confidence: 99%
“…The most frequently used features in the BCI systems are: AR coefficients [3], [4], [5], [6], AR models with exogenous inputs [6], power spectral parameters [8], [7], [9], [10], [11], statistic phase synchronization [8], [9], spatial filtering [12], mean value of the phase coherence [8], discharge frequency of a neuronal group [15], P300 wave [12], [13], [14] etc. This paper focuses on the same issue, namely that of finding more appropriate EEG features for cognitive tasks applications.…”
Section: Introductionmentioning
confidence: 99%